1992
DOI: 10.1088/0022-3727/25/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Ion currents to cylindrical Langmuir probes in RF plasmas

Abstract: The positive ion current collected by cylindrical Langmuir probes has been measured in an RF argon plasma. The current-voltage characteristics were measured using an RF compensation technique whereby the probe was forced to follow the RF fluctuation in the local plasma potential. The I-V curves from probes of different radii and material show an ion current which is always greater than that predicted by the orbital motion theory and that agrees well with the radial motion theory. This is because the ions trave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 17 publications
(1 reference statement)
7
86
1
Order By: Relevance
“…Ion currents collected by cylindrical Langmuir probes with radii a $ k D in low-pressure argon and neon RF plasmas are in excellent agreement with the cold-ion ABR theory 23,24 for temperature ratios at least as high as T e =T i ¼ 0:3. 24 A lowpressure helium plasma begins to depart from the ABR theory for these elevated temperature ratios due to the enhanced thermal velocity of the light helium ions which causes nonnegligible angular motion.…”
Section: Modelsupporting
confidence: 58%
“…Ion currents collected by cylindrical Langmuir probes with radii a $ k D in low-pressure argon and neon RF plasmas are in excellent agreement with the cold-ion ABR theory 23,24 for temperature ratios at least as high as T e =T i ¼ 0:3. 24 A lowpressure helium plasma begins to depart from the ABR theory for these elevated temperature ratios due to the enhanced thermal velocity of the light helium ions which causes nonnegligible angular motion.…”
Section: Modelsupporting
confidence: 58%
“…For OML theory to apply, the effective radius r eff must be smaller than both the Debye length k D and the mean free path k coll for elastic ion-neutral collisions. 32 Both conditions are satisfied, with typically more than an order of magnitude, for all cases reported in this work.…”
mentioning
confidence: 74%
“…For a negatively biased probe and in a medium pressure discharge, none of the present theories for the ion current collected by a probe describe the experimental results [1][2][3][4][5][6][7] accurately. Sudit and Woods4 and Sternovsky et al [6][7][8] have found discrepancies of a factor of 10 between ion densities determined from the ion part of the probe characteristic using orbital motion limited (OML) theory [9,10] and the densities as measured with microwaves or from the electron part of the probe characteristic.…”
Section: Introductionmentioning
confidence: 83%